Qualified audit reports of local authorities in the northern states of Malaysia - Ibrahim, Mohammad Azhar; Engku Ali, Engku Ismail; Syed Ismail, Syed Soffian; Bidin, Zainol (Universiti Utara Malaysia, 2004)
The reliability of information presented in the financial reports of local authorities is of utmost importance to enable the public to measure their performance in terms of efficiency and effectiveness in using public resources. The task to provide such an assurance lies with the Auditor General, who has been entrusted to enforce the auditing compliance regulations. A certificate in the form of “unqualified,” “qualified,” “adverse,” or “disclaimer” accompanied by a report on the financial affairs of the local authorities concerned will be issued after the Auditor General completes the audit of the local authorities’ financial statements. Our study on 14 local authorities comprising municipal and district councils in the Malaysian States of Perlis, Kedah and Penang found that the Qualified Certificate is the common type of audit certificate issued to the local authorities concerned during the period 1997-2001(inclusive of both years). Discrepancies in “Fixed Assets Register” ranked first among the audit incidents that led towards non-compliance to the audit procedures. This was followed by discrepancies in “Other Receivables” and “Cash Flow Statements” which ranked second and third positions respectively. Our finding also shows that size does not grant any advantage to the bigger local authority in reducing the number of audit incidents.